ANALISIS FAKTOR KUALITAS PELAYANAN PERPUSTAKAAN SMK TEUKU UMAR SEMARANG MENGGUNAKAN MODEL KANO - Angga Dwi Ardianto; Ahmad Saeroji (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The library of SMK Teuku Umar is located in Semarang City with a total of 627 students, and it should have high customer potential. However, student visits to the library are still fluctuating and tend to be low, with an average of only 100 students per month. Based on this problem, an improvement in service quality was carried out using the Kano Model and the Service Quality method. This study uses a quantitative approach. This study aims to determine the quality of service and provide improvement suggestions to enhance the service quality of the SMK Teuku Umar Semarang Library. The research population consists of 244 students from grades X, XI, and XII, all of whom were used as samples. Data were collected through a Likert scale questionnaire. The results of the Service Quality analysis show that the service quality score is 0.99, which means the service does not yet meet customer expectations. Through the Kano Model analysis, service attributes are classified into Must Be, One Dimensional, Attractive, Indifferent, and Reverse categories. The results of the analysis from both methods show that there are 12 attributes that need to be maintained and 3 attributes that need to be improved. There are several suggestions for improvements that can enhance service quality at SMK Teuku Umar Semarang Library, such as improving the quality of supporting facilities, librarian behavior, and environmental cleanliness.